Concept Attainment Model: Fostering Science and Mathematics Learning in Students with Visual Impairment - Chaudhary, Seema; Pandey, Yogendra (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Teaching Science and mathematics to students with visual impairment is very challenging. The importance of science and mathematics learning in students with visual impairment is now recognised by all educationists. Science and mathematics is an important subject of school curriculum and is also important in daily living as well as in the study of other subjects. This paper is an attempt to understand the problem of visually impaired students in learning science and mathematics and foster their Science and mathematics learning with the help of concept attainment model. Science and mathematics learning today is becoming increasingly complex and abstract. It is therefore important that new methods and techniques i.e. concept attainment model of teaching must be introduced in order to make the teaching of science and mathematics learning in students with visual impairment more effective and efficient.